Traveling in the Qur'an (A Study of the Interpretation of the Verses of Rihlah and Safar from the Perspective of Tafsir Al-Misbah) - Muhammad Izza Anandya; Ipmawan Muhammad Iqbal; Murdianto (al-Afkar, Journal For Islamic Studies, 2026)
This study discusses the concept of travel (rihlah and safar) in the Qur'an with a thematic interpretation approach using Tafsir Al-Misbah by M. Quraish Shihab as the main source. The background of this study rests on the phenomenon of increasing human needs for travel activities as a form of physical and spiritual refreshment, especially in the face of modern life pressures. Traveling in an Islamic perspective is not only understood as a recreational activity, but also as a form of worship, knowledge seeking, and spiritual contemplation. This research uses a literature study method with a qualitative approach to examine the meaning and implementation of the verses of rihlah and safar comprehensively. The results show that the Qur'an provides guidance and relief for Muslims in the context of safar, both in the implementation of worship and social interaction. Quraish Shihab's interpretation emphasizes that Islam is a religion that is adaptive, easy, and responsive to the dynamics of human life, including in the context of travel. Thus, traveling in the Qur'an is not just a physical movement, but also a medium to increase faith, broaden horizons, and be grateful for the blessings of Allah subhanahu wa ta'ala.